Learning from Caretta caretta (Linnaeus, 1758) epibionts: a study from the Adriatic Sea - Baruffaldi, Matilde; Rubini, Silva; Ignoto, Sara; Angelini, Valeria; Tiralongo, Francesco (Frontiers in Marine Science, 2023)
Epibiont communities can be used as useful ecological indicators, providing information on the ecology and health conditions of their hosts. In this study, we analyzed the cirriped community from a total of 117 dead specimens of Caretta caretta (Linnaeus, 1758) collected in the north Adriatic between the years 2020 and 2022. We recorded a total of six different species distributed in five genera of cirripeds. The two most abundant species were Chelonibia testudinaria (Linnaeus, 1758) and Platylepas hexastylos (Linnaeus, 1758), located in different areas of the body; the former mainly on the carapace, while the latter mainly on the skin. We analyzed their abundance and distribution pattern on the sea turtle’s body and used the findings to deduce the health conditions and ecological aspects of stranded specimens of C. caretta, providing new data on this threatened and vulnerable species and its epibionts. A total of 11 specimens of C. caretta were affected by DTS (Debilitative Turtle Syndrome), these specimens exhibited a significant barnacle infestation on all body parts, markedly higher than the specimens of C. caretta not affected by DTS. Studies of associated barnacles in sea turtles should be encouraged among researchers as complementary tool to infer habitat use and health status of sea turtle species.